POETRY OF FOOTNOTES. CZESŁAW MIŁOSZ’S THE RISING OF THE SUN - Okulicz-Kozaryn, Radosław (Porównania, 2012)
Miłosz’s poem From the Rising of the Sun is said to encapsulate the most important features of his poetry. In his paper entitled The poetry of footnotes, Radosław Okulicz-Kozaryn shows that this opinion about the poetry of Miłosz is based rather on the critics’ intuition than contextual interpretation, thorough analysis or even close, comprehensive reading of his poem. Moreover, the closer the reading the more troublesome the question of understanding the poem becomes, as in some fragments (which do not have editorial notes) the Polish language is interwoven with excerpts in Lithuanian or old Balto-Russian. Leaving some of them only in their original form as an irreducible lyrical value, he also quotes from other minor Polish-Lithuanian authors and provides information about them. Milosz also includes some detailed explanation of the forgotten region of Lauda. The word “footnotes” is marked out with caps, thus being imbued with the importance of the constructional element of his work. Besides, Miłosz adapts an old form of silva rerum and meanwhile, by mentioning Mickiewicz’s poem Grażyna, he evokes the tradition of romantic tales in which notes were originally conceived as an integral part of the poetical work.